Exchange rate variability and the riskiness of U.S. multinational firms: Evidence from the breakdown of the Bretton Woods system - Bartov, Eli; Bodnar, Gordon M.; Kaul, Aditya (Journal of Financial Economics, 1996)
We examine the relation between exchange rate variability and stock return volatility for U.S. multinational firms and decompose this relation into components of systematic and diversifiable risk. Focusing on two five-year periods around the 1973 switch from fixed to floating exchange rates, we find a significant increase in volatility of monthly stock returns corresponding to the period of increased exchange rate variability, even relative to the increase in stock return volatility for three control samples. In conjunction with this increase in total volatility there is also an increase in market risk (beta) for multinational firms.